Socio‐economic differentials in the health‐related quality of life of Australian children: results of a national study - Nicola J. Spurrier; Michael G. Sawyer; Jennifer J. Clark; Peter Baghurst (Elsevier, 2003)
Abstract Objective: To examine differences in health‐related quality of life (HRQL) of children living in different socio‐economic contexts in Australia. Methods: Parental reports describing the HRQL and socio‐economic status of a random national sample of 3,597 school‐age children were obtained using the Child Health Questionnaire (CHQ) and a standardised socio‐economic interview. Response rate was 70%. Results: Children in families of higher income, whose parents had more years of schooling and were employed and children who lived in two‐parent, original families had significantly higher HRQL across a range of domains assessed by the CHQ. Conclusion: Children from lower socio‐economic backgrounds in Australia have a significantly more negative experience of health and wellness. Such differences may well increase unless deliberate political attention is given to addressing the widening differences in relative wealth in Australia.